Produktivitas dan Pendapatan Usahatani Jagung di Desa Sei Beras Sekata, Kecamatan Sunggal, Kabupaten Deli Serdang - Sitohang, Maryanti; Nainggolan, Mai F Fernando; Saragi, Cyprianus P.H (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Corn is one of the food crop commodities in the agricultural sector that is widely cultivated by farmers in Indonesia. Corn is included in the National food group which is the main staple food after rice so it is called a buffer for National food security. This research aims to analyze land productivity and corn farming income/Ha/MT in Sei Beras Sekata Village, Sunggal District, Deli Serdang Regency. The research methods used were observation, interviews and questionnaires. The data analysis used is productivity and income analysis. The results of the research show that the productivity of corn farming in Sei Beras Sekata Village, Sunggal District, Deli Serdang Regency is 6 tons//Ha/MT and the average level of corn farming income per hectare is IDR 9,627,123.